The effectiveness of parameter mapping in sonifying 3D body movements - Hanafi Atan; Fauziah Sulaiman; Rozhan Mohd. Idrus (2013)
Most of instructions by trainers or physiotherapists in body movements are mostly done through voice instructions or touches. To follow these instructions without seeing it is not easy especially for blind people. It is hoped by only listening to the non-speech sounds, a person should be able to follow the exact body movements. Thus, this paper explains the potential of using non-speech sound to represent 3D body movements. The conversion data-to-sound technique to be used is Parameter Mapping, where the movement properties will be mapped with sound properties. The experimental results will also be discussed.